Economic Benefit from Nutrigarden to Farmwomen of Wanaparthy District, Telangana, India - , Gottemukkula Bhavani; , Rondla Anitha; , Shakir Ali Qayyum Ali Syed (Archives of Current Research International, 2024)
Nutri-garden is an important concept that helps to combat malnutrition by producing diverse kinds of vegetables for rural families. YFA-KVK, Mahabubnagar-I demonstrated the Nutrigarden concept amongst 100 families of three mandals namely Madanapuram Kothkota and Wanaparthy of Wanaparthy district. The present study was taken-up to analyze the economic impact of the Nutrigarden along with perceived constraints faced by the farmwomen. The demonstrations on Nutrigarden improved their understanding in successful adoption of the concept. The total beneficiaries covered were 100 with an area of 1000sq.meters each, which accounts to 10 ha. as a whole. From this said area farm women as a whole were able to generate a total amount of Rs. 30592.09/- from kharif vegetables and Rs. 26604.78/- from rabi vegetables. Therefore, the total income from vegetable was Rs. 57196.87/- from an area 10 ha. Including both the seasons excluding home consumption. Besides, there are few perceived constraints in successful adoption of Nutrigarden. Overall analysis revealed that time consuming, lack of backyard and front yard space availability for Nutrigarden, Unaware of the economic advantage of Nutrigarden and lack of knowledge on pest and disease management were amongst the major constraints as perceived by farmwomen.